Sedimentology of terrigenous mud from the Orange River delta and the inner shelf off Namaqualand, South Africa - Mabote, M.; Rogers, J.; Meadows, M. E. (South African Geographical Journal, 1997)
Sediment cores, from the inner shelf off the Namaqualand continental shelf have been examined using radiographic and grain-size techniques. Size-frequency distributions reveal that the sediments are poly modal, with a dominant very fine-silt mode being between 8-4μm, and suggest that the weak, poleward-flowing De Decker Current causes southward dispersal of terrigenous mud off the Orange River mouth. It appears that this current is not strong enough to transport material coarser than very fine silt. Material >63μm in size is rare, but may be indicative of storm events. Quartz and mica in the sediments are related to the semi-arid climate of Namaqualand, where they are entrained by adiabatic Berg winds moving offshore from the interior. Sponge spicules indicate the presence of filter-feeding animals (epifauna). Planktonic foraminifera may be indicative of relatively high productivity associated with nutrient-rich upwelling waters, which support an enormous population of plankton. The presence of faecal pellets is associated with the presence of burrowing infauna. Authigenic gypsum is associated with the presence of anaerobic conditions in the sediments. Two of the lithofacies identified in these fine-grained deposits are: (a) laminated mud and (b) homogeneous mud. Primary sedimentary structures are present, particularly in the portion of the mudbelt closest to the Orange Delta, where the mud is well laminated. Laminations decrease in abundance southward from the delta, where the muddy sediment is increasingly bioturbated (burrowed) by infauna, probably by polychaete worms.
id: 218